Academic scientists' scholarly use of information resources in the digital environment: Perceptions and barriers. Issue 6 (16th October 2018) - Arshad, Alia; Ameen, Kanwal
Abstract : Purpose: The purpose of this study is to investigate the academic scientists' scholarly use of information sources, the disciplinary differences in their use and the barriers encountered, particularly while using journals. Design/methodology/approach: A quantitative research design based on the survey method was used to achieve the objectives of this study. A self-administered questionnaire was distributed to all the academic staff of three disciplines – science, life sciences and pharmacy. Together, they constituted 24 departments of the University of the Punjab. This oldest and largest public sector university was selected as a sample. Findings: The findings showed that e-journals, e-reports and online reference sources were frequently used. The disciplinary differences were found with regard to the use of e-journals and e-books. Users of e-journals lacked skills of advanced searching and were not able to determine the quality of e-journals. Respondents faced certain barriers in usage such as payment of e-journal articles not available through the Library, slow internet speed and lack of information literacy instructions program. Originality/value: Previous researchers conducted studies that were focused mostly on the academic scientists' perceptions and the extent of electronic information sources' use. Researchers in Pakistan mostly examined students and research scholars' use of electronic information sources and very few studies were conducted to investigate academic scientists' scholarly information seeking behavior. This study is valuable, as it investigated the scholarly use of information sources by academic scientists and particularly disciplinary differences in their use, digital literacy skills and the barriers encountered while using e-journals.